Formation and Change of Maternal Identity in Twins Pregnancy - Tokiwa, Yoko; Yano, Keiko; Ohwada, Nobuo; Imazeki, Setsuko (Kita Kantō igaku (The Kitakanto Medical Journal), 2002)
Background and Objectives : This study is to identify maternal identity during pregnancy and study formation and change in the identity of mothers of twins to develop psychological support for them. Subjects and Methods : Subjects were 13 women pregnant with twin fetuses who provided informed consent. Nine were primiparas and 4 multiparas. Semiconstitutive interviews were made on maternal identity and feelings to word babies during early, middle, and late pregnancy. The study was conducted between January and May 1999. Two questions were asked on maternal identity “How do you feel what be coming a mother?” and “At what time did you become aware that you were a mother?”. Questions on feelings to word the babies were “When did you feel the presence of 2 infants?”, “What are your feelings toward each baby?” and “What are your concerns about delivery and childcare ?” Results : During early pregnancy, they had no clear idea that they were having twins. Maternal identity emerge when they were informed they would have twins by doctors at regular checkups, and shown the 2 babies by echography and/or had of multiple fetuses confirmed. As in single pregnancies mothers, expressed specific feelings toward each baby as they become aware of fetal movement. Their awareness was intensified if problems emerged concerning continuation or development of the fetus. If there are any problems of mothers and/or fetus identified, psychological support should be provided as well as obstetrical management by doctors. In late pregnancy, doctors informed mothers of plans for delivery, intensifying maternal identity. Multiple pregnancy presents a marked increase in abdominal size, causing problems such as low back pain, gastric discomfort and frequent urination. Mothers also expected to feel more psychological stress since they felt they had to do their best for the sake of their babies. It appears that multiple pregnancy therefore affects the formation of maternal identity. Maternal identity of women with multiple fetused is formed by the ultrasound image before they become aware of fetal movement. After fetal movement becomes obvious, maternal identity is influenced by fetal development and health. With delivery plans presented, they have more concrete image of childcare, enabling them to prepare to be the mother of twins.